A Novel, Robust Method of Measuring IMT(intima-media thickness) Using Graph Cut and Snake Model in Ultrasound Imaging - Seo, Jae-Eun; Lee, Deuk-Hee (2012 12TH INTERNATIONAL CONFERENCE ON CONTROL, AUTOMATION AND SYSTEMS (ICCAS), 2012)
For many years, researchers who try to find the grounds for specific diseases have continued using ultrasound images. Particularly, there have been efforts to measure intima-media thickness(IMT) in ultrasound images. A lot of studies have focused on finding a robust method to measure IMT, but the methods that have been found aren't perfect for measuring the IMT and they erase the speckle noise, which is an important interference factor [20-21]. Here, we would like to suggest a new approach to measure the IMT, a method that dose it more robustly. In order to measure the IMT, we make a snake model using the graph cut method in a color Doppler image. From the color region, we are able to suggest a region to use to find an initial region that is applied to find the carotid artery vessel, determine, the background features of the graph cut, and initialize the points of the snake method. In this paper, we describe the theoretical background for measuring the IMT and we show the process of our method. Finally, we present the results of experiments that were conducted to test our method and evaluate those experimental results.